Adducin‐1 Facilitates Influenza Virus Endosomal Trafficking and Uncoating by Regulating Branched Actin Dynamics and Myosin IIB Activity - Meijun Jiang; Jiahui Zou; Yaoming Jin; Chenjun Jiang; Shaoyu Tu; Tong Chen; Jinli Guo; Yanqing Cheng; Meilin Jin; Huanchun Chen; Hongbo Zhou (Advanced Science, 2025)
Abstract Actin‐ and microtubule‐based transport systems are essential for the trafficking of endocytic viruses and cargoes. Microtubules facilitate long‐distance transport; however, the precise role of actin dynamics and its regulators during virus entry, particularly in the transit process, remains elusive. Here, Adducin‐1 (ADD1) is identified as a key regulator of actin dynamics, as demonstrated by real‐time monitoring of quantum dot (QD)‐labeled influenza A virus (IAV) movement. ADD1 deletion increases actin density around endocytic vesicles, disrupting general vesicular trafficking and inhibiting the replication of diverse endocytic viruses. Mechanistically, endocytic viruses or cargoes trigger the phosphorylation of ADD1 at Ser726, which reduces the density of actin branches for effective transport. Additionally, the physical force required for IAV capsid dissociation is influenced by ADD1. Collectively, the study identifies a basic actin dynamics event with broad relevance to endocytic viruses or cargo trafficking and represents ADD1 as a potential target for developing broad‐spectrum antiviral strategies.